Academic freedom, institutional autonomy, and public accountability in the context of the democratisation and transformation of education - Majozi, P. J.; Kula, T, J; Sibiya, T. E.; Makondo, L. (South African Journal of Higher Education, 2025)
In South Africa, academic freedom grants higher education institutions independence and autonomy. Section 16(1) of the South African Constitution enshrines the right to freedom of expression, which includes academic freedom and freedom of scientific research. This article explores the conceptualisation of academic freedom, emphasising its role in safeguarding both the right and its protection. Recognising that education has historically been shaped by political forces, the Constitution aims to transform society from authoritarianism to constitutional democracy, raising critical questions about the systemic organisation of education and training in a post-apartheid context. The article critically examines the intersection of academic freedom, institutional autonomy, and public accountability within the democratisation and transformation of higher education. Drawing from scholarly perspectives, it interrogates market-promoting policies in the Technical and Vocational Education and Training (TVET) sector, highlighting the tension between neoliberal agendas and the democratic ideals envisioned for post-apartheid education. Using a governmentality lens, the article questions how public accountability extends beyond financial transparency to encompass the social transformation role of educational institutions. Adopting a Human Rights-Based Approach, the article argues that achieving social justice and socio-economic transformation in education requires moving beyond prescriptive, market-driven policies that undermine institutional autonomy. It concludes that sustainable public interests can only be realised through a comprehensive overhaul of the current system.